IMF Survey, Volume 31, Issue 12. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2002)
Corporate profitability is a source of uncertainty in a generally positive global market outlook, IMF International Capital Markets Department Head and Counsellor Gerd Hausler said at a June 12 press conference. Summarizing the findings (see charts, pages 194-95) of the IMF's second Global Financial Stability Report, he noted that 'the near-term outlook in mature markets is largely free of imminent threats, mainly because the world economy has recovered and has helped build support also for financial markets.' However, emerging markets in South America have come under recent pressure. This report is designed to 'detect fault lines in global financial markets,' and a theme running through this issue is the uncertainty posed by the level and quality of corporate profits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet